ماثور درود وسلام میں رسول اللہﷺ کےاسمائے گرامی اور ان کی معنویتNames of the Holy Prophet and their Effectiveness in the Authentic Durood and Salām (Al-Qamar, 2021)
Sending Durood-u-Salam (peace and divine blessings of Allah) to Muhammad (SAW) is a very blessed and rewarding act along with the command of Allah, on which various aspects many leading and later scholars has written a lot, is being written continually and this process will be continued till the Day of Judgement. In this article, some of the words of the eminent Durood-o-Salam and the meanings of their selected and specific eminent names of the Holy Prophet (SAW) are highlighted. For this purpose, two words of Salat-o-Salam, which are mentioned in Sahih or Hasan Ahadith: Salat-o-Salam and five names of Rasool-u-Allah: Muhammad, Al-Rasool and al-Nabi have been selected. The article is consisting of three topics that are: the literal and shar'i meaning of Salat-o-Salam and its characteristics and meaning, extraction of the mentioned ahaadeeth of five names and the meaning, characteristics, and concept of each name. At first, the relevant hadith has been extracted respectively in the article, then explaining the meaning of the given name in it and later the characteristic and meaning of this name is argued from the Qur'an and Sunnah, the books of the dictionaries and the declaration of the ummah, according to narrative, inductive, derivative, and analytical methodology research, and style. In doing so, an attempt has been made to make it manifest in the practical life of the Prophet (SAW). At the end of article, the results of the research and recommendations are written.
Keywords: Effectiveness of Salat and Salam; Muhammad; Rasool; Nabi; Practical life; highlighting